Influence of neuroscience and the seven learnings in the teaching learning process and the academic performance - Pizano Chávez, Guillermina (2014)
The study of Neuroscience and The seven Learnings introduce Neuroscience as the new paradigm that enables to analyze and explain the intelligent human behavior. The discoveries found in this field have been shown not only in the theory but in the pedagogical practice as well. In the first case, one of the most recent theories about intelligent behavior has been conceived from the perspective of neuroscience (science that studies HUMAN BRAIN). (Beauport and Diaz, 1994) This study has given more relevance to the relation between the function of the brain and human behavior as well as the conditions that lead to an efficient teaching – learning process. In this context, we introduce The seven Learnings, described by Edgar Morin that state central problems which have been ignored and that are necessary in order to reach a successful teachinglearning process in this century. These seven Learnings must be analyzed in any society or culture. Besides, the scientific basis of this study, remarks some deep mysteries about universe and life.